The Phenomenon of Drug Emulsion Carriers Compaction during Their Movement in Microstructures - Mariola M. Błaszczyk; Jerzy Sęk; Łukasz Przybysz (MDPI AG, 2022)
The greatest challenges of modern pharmacology are the design of drugs with the highest possible efficacy of an active substance and with the lowest possible invasiveness for the whole organism. A good solution features the application of a bioactive substance in different carriers. The effectiveness of such preparations is determined not only by the properties of the drug, but primarily by the dynamics of carrier movement in the body. This is the reason why studies on the dispersed systems transport in micro- and nanostructures are becoming important. This paper presents a study of emulsion systems transport in microcapillaries. A dispersed phase thickening effect was observed during the process, which resulted in a concentration increase of the flowing emulsion, in some cases up to 10 times. This phenomenon directly influences transport dynamics of such substances in microstructures and should be taken into account when designing drug parameters (concentration, release time, and action range). The effect was investigated for three different emulsions concentrations and presented quantitatively. The scales of this phenomenon occurrence at different flow conditions were investigated, and their magnitudes were modelled and described. This allows the prediction of the flow resistance in the movement of given dispersion systems, as a function of the flow rate, the emulsion parameters, and the microchannel size.